2004
DOI: 10.1089/1075553041323902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Qi Therapy (External Qigong ) on Premenstrual Syndrome: A Randomized Placebo-Controlled Study

Abstract: Qi therapy may be an effective complementary therapy for managing the symptoms of PMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…3,4,27,28,30 External qigong has similar features as other forms of energy healing-for example, therapeutic touch, Reiki. The effect sizes (ES) of external qigong in this review (ES ϭ 1.53 compared with general care 14,29 and 0.63 for placebo 10,13 ) seem larger compared with those of similar therapies. 2,24 However, due the use of different assessment measures for evaluating pain and the use of different controls, such comparisons are problematic.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…3,4,27,28,30 External qigong has similar features as other forms of energy healing-for example, therapeutic touch, Reiki. The effect sizes (ES) of external qigong in this review (ES ϭ 1.53 compared with general care 14,29 and 0.63 for placebo 10,13 ) seem larger compared with those of similar therapies. 2,24 However, due the use of different assessment measures for evaluating pain and the use of different controls, such comparisons are problematic.…”
Section: Discussionmentioning
confidence: 63%
“…Sufficient details of dropouts and withdrawals were described in 3 trials. 10,11,29 Only 2 trials 11,14 reported details on allocation concealment. OPVS scores ranged from 7 -13 of a maximum of 16.…”
Section: Study Quality and Validitymentioning
confidence: 99%
“…176 The evidence-based reviews concluded that RCTs have not suggested consistent benefit for Ginkgo biloba, evening primrose oil and homeopathic treatments but that initial positive RCTs suggest further study of massage, 177 reflexology, 178 chiropractic manipulation 179 and biofeedback. 180 Small RCTs have reported that saffron 181 and Qi therapy 182 were each superior to placebo in women with prospectively confirmed PMS. There have been positive open reports, but no RCTs, with Hypericum, 183,184 yoga, 185 guided imagery, 186 photic stimulation 187 and acupuncture.…”
Section: Herbal Complementary and Other Treatmentsmentioning
confidence: 99%
“…It is worth emphasizing that pain was diminished significantly among low back pain sufferers, woman with pre-menstrual symptoms (Jang and Lee, 2004), and chronic pain patients . Moreover, Qi Gong's multidimensional influence on the whole person should be acknowledged as a standard method of rehabilitation, health promotion and prevention.…”
Section: Clinical Applications Of Qi Gongmentioning
confidence: 99%